Frost resistance and improvement techniques of recycled concrete: a comprehensive review - Ma, Quan; Duan, Zhenhua; Wang, Jun; Yin, Gang; Li, Xi (Frontiers in Materials, 2024)
In the pursuit of sustainable construction practices, the utilization of recycled concrete has emerged as a pivotal strategy, distinguished by its commitment to resource conservation and environmental stewardship. Nevertheless, the inherent micro-porosity and micro-cracking within the old mortar of recycled concrete may lead to weak bonding performance at the interfacial transition zone, culminating in diminished strength, reduced density, and elevated water absorption rates compared to conventional concrete, which critically impairs its performance in cold climates subjected to freeze-thaw cycles. Consequently, this paper provides a structured examination of the frost resistance properties of recycled concrete subjected to freeze-thaw cycling. Initially, the study delineates the mechanisms of frost-induced damage in recycled concrete by synthesizing the degradation pathways observed in both conventional and recycled concrete during freeze-thaw exposure. Subsequently, a detailed analysis is conducted to identify the pivotal factors affecting frost resistance, encompassing the proportion and moisture affinity of recycled aggregates, the addition of silica fume and fly ash, the water-to-cement ratio, and the degree of water saturation. In the final segment, the study compiles and reviews the strategies for bolstering the frost resistance of recycled concrete, including the incorporation of air-entraining admixtures, fiber reinforcement, and aggregate modification approaches. The objective of this research is to offer a thorough comprehension of recycled concrete, with a concentration on the mechanisms of frost damage, the critical determinants of frost resistance, and interventions to augment its resilience against freezing conditions. On this basis, the present paper, in conjunction with the characteristics and current research status of recycled concrete, proposes recommendations for the application of recycled concrete in cold regions. This review is anticipated to facilitate researchers in gaining a comprehensive understanding of the freeze-thaw characteristics of recycled concrete and the measures to enhance its frost resistance. Furthermore, it aims to assist engineering and technical personnel in selecting appropriate treatment methods to improve the frost resistance of recycled concrete in cold regions, thereby promoting the practical engineering application of recycled concrete in such areas.